Catalyst for improving discharge performance of metal fuel cell through phase change of rare earth-induced manganese-based material and preparation method of catalyst

By doping rare earth cerium into manganese dioxide catalyst, the phase change is induced by hydrothermal method, and the conversion from β phase to α phase is solved, which solves the problems of poor conductivity and low catalytic activity of manganese dioxide, which significantly improves the metal fuel cell Discharge performance.

CN119447332APending Publication Date: 2025-02-14HAINAN UNIV +1

Patent Information

Application Number
CN202411566781.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, manganese dioxide catalyst has poor electrical conductivity and low catalytic activity, which cannot meet the actual needs of metal fuel cells.

Method used

The tetravalent rare earth cerium is doped into a manganese-based material by hydrothermal method, inducing the conversion of manganese dioxide from a stable but poor electrocatalytic β phase to an alpha phase with higher activity and better conductivity.

Benefits of technology

The electrochemical activity of the material is improved, the catalytic performance of the oxygen reduction reaction is improved, and the discharge performance of metal fuel cells is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447332A_ABST
    Figure CN119447332A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for improving discharge performance of a metal fuel cell through phase change of a rare earth induced manganese-based material and a preparation method, tetravalent rare earth cerium is doped into the manganese-based material through a hydrothermal method, uniform combination of cerium and manganese dioxide is realized in the process, crystal phase transformation of manganese dioxide is successfully induced, and the discharge performance of the metal fuel cell is improved. Beta-phase MnO2 which is stable but poor in electro-catalytic performance is converted into alpha-phase MnO2 with higher activity and better conductivity. The phase change greatly improves the electrochemical activity of the material. The number of active sites is insufficient due to the compact crystal structure of the beta-phase MnO2, and the open structure of the alpha-phase MnO2 increases the surface area and the reaction active sites, so that the catalytic performance of the oxygen reduction reaction is optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical catalysis, and in particular, relates to a catalyst for improving the discharge performance of a metal fuel cell by inducing phase change of a rare earth-induced manganese-based material and a preparation method thereof. Background Art

[0002] As a green electrochemical energy source, metal fuel cells have attracted widespread attention and have great development prospects due to their high energy density, high intrinsic safety, environmental friendliness, and abundant resources. Metal fuel cells are composed of a metal negative electrode, an air electrode (positive electrode), and a neutral or alkaline electrolyte. The negative electrode is composed of metals, usually metals such as zinc, magnesium, and aluminum, or alloys. The air electrode is the site of oxygen reaction, and is generally composed of a catalyst layer, a conductive current collector, and a waterproof and breathable layer. Taking aluminum-air batteries as an example, during the discharge process, metal aluminum is continuously consumed and Al(OH)3 is generated, while oxygen diffuses to the three-phase reaction interface of the air electrode to undergo an oxygen reduction (ORR) reaction.

[0003] The air electrode plays a decisive role in the electrochemical performance of its metal fuel cell, and the performance of the air electrode depends largely on the selected cathode catalyst, whose activity and stability directly affect the discharge voltage, power density and service life of the battery. Commonly used metal fuel cell catalysts include precious metal catalysts, metal oxide catalysts, spinel catalysts, perovskite catalysts, etc. Among them, platinum and silver are used more frequently, have high catalytic activity and relatively stable performance, but they are expensive and resource-scarce, making them difficult to commercialize on a large scale. Manganese dioxide catalysts have broad development and application prospects due to their abundant raw materials, low cost, and relative non-toxicity. However, manganese dioxide itself has poor conductivity and low catalytic activity as an air electrode catalyst, which cannot meet the needs of actual use.

[0004] Patent CN105261768B discloses a method for preparing a rare earth modified manganese dioxide / carbon composite catalyst for metal-air batteries, in which potassium permanganate aqueous solution, sulfur-containing amino acids, lanthanum salts, carbon materials and other materials are mixed, washed and dried, and calcined at high temperature to obtain a composite ball with surface wrinkles formed by uniformly mixing lanthanum-doped manganese dioxide nanosheets and carbon materials. Although this method uses rare earth element doping, it mainly modifies the layered manganese dioxide by doping with lanthanum, and no phase change of manganese-based materials occurs, and its catalytic performance still needs to be further improved.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art, provide a catalyst and a preparation method for rare earth-induced phase change of manganese-based materials to improve the discharge performance of metal fuel cells, and solve the problems raised in the above-mentioned background technology.

[0007] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0008] A method for preparing a catalyst for improving the discharge performance of a metal fuel cell by inducing phase change of a rare earth-induced manganese-based material, comprising the following steps:

[0009] Step (1): preparing a monohydrated manganese sulfate solution, and adding ammonium persulfate and ammonium sulfate according to a molar concentration ratio, and magnetically stirring until the solution is completely dissolved to form a mixed solution ①;

[0010] Step (2): adding cerium nitrate according to the molar ratio to the mixed solution ① obtained in step (1), and continuing stirring for 1-2 hours, and mixing evenly to obtain a mixed solution ②;

[0011] Step (3): transferring the rare earth doping precursor solution obtained in step (2) to a hydrothermal reaction vessel for hydrothermal reaction;

[0012] Step (4): After the hydrothermal reaction is completed, the reaction product is centrifuged and washed with deionized water and ethanol to remove impurities. Subsequently, after cooling, the reaction product is centrifuged, washed with deionized water and ethanol, and dried in a vacuum oven at 50-80°C for 8-12 hours. After drying, the final α-MnO2 nanorod catalyst is obtained.

[0013] Optionally, the molar concentration ratio of the manganese sulfate monohydrate solution, ammonium persulfate and ammonium sulfate used in step (1) is 1:1:2.

[0014] Optionally, the magnetic stirring time in step (1) is 0.5-2h.

[0015] Optionally, the molar ratio of cerium nitrate to mixed solution ① in step (2) is (0.1-0.5:1).

[0016] Optionally, the hydrothermal reaction temperature in step (3) is 120-140° C., and the reaction time is 10-12 h.

[0017] Optionally, the catalyst in step (4) has a rod-shaped nanostructure with a particle diameter of 20-50 nm and a length of 100-600 nm.

[0018] Optionally, the vacuum temperature in step (4) is 50-80° C., and the drying time is 8-12 hours.

[0019] A catalyst prepared by the method for rare earth induced phase change of manganese-based materials to improve the discharge performance of metal fuel cells.

[0020] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all the advantages described below at the same time:

[0021] 1. The present invention doped tetravalent rare earth cerium into manganese-based materials through a hydrothermal method. This process not only achieved a uniform combination of cerium and manganese dioxide, but also successfully induced a crystal phase transition of manganese dioxide, from stable but poorly electrocatalytic β-phase MnO2 to α-phase MnO2 with higher activity and better conductivity. This phase transition greatly improves the electrochemical activity of the material. Due to its compact crystal structure, β-phase MnO2 has an insufficient number of active sites, while the open structure of α-phase MnO2 increases the surface area and reactive sites, optimizing the catalytic performance of the oxygen reduction reaction.

[0022] 2. The preparation method of the rare earth induced manganese-based material phase change catalyst provided by the present invention is synthesized by hydrothermal method, which is simple and easy to implement and can be synthesized on a large scale. The prepared manganese dioxide material is transformed from β-phase MnO2 to α-phase MnO2, and the prepared manganese dioxide has a rod-like structure, a particle diameter of 20-50nm, a large specific surface area, and can provide more active sites.

[0023] 3. The optimal ratio of cerium (IV) to manganese dioxide was obtained by adjusting the ratio of rare earth salts and the reaction temperature. The test showed that the catalytic performance of the catalyst was improved compared with that of β-phase MnO2 without cerium (IV), and the prepared air electrode had excellent discharge performance in alkaline aluminum-air batteries.

[0024] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings described below are only some embodiments. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0026] Figure 1 TEM morphology of the rare earth Ce-doped manganese dioxide (Ce-MnO2) catalyst prepared in Example 3 of the present invention;

[0027] Figure 2 The XRD pattern of the Ce-MnO2 catalyst prepared in Example 3 of the present invention;

[0028] Figure 3 The oxygen reduction (ORR)-LSV performance curve of the Ce-MnO2 catalyst prepared in Example 3 of the present invention;

[0029] Figure 4The aluminum-air battery prepared by the Ce-MnO2 catalyst prepared in Example 3 of the present invention has a high conductivity at 20 mA cm -2 Discharge performance curve under current density;

[0030] Figure 5 The discharge performance curves of the aluminum-air battery prepared with the Ce-MnO2 catalyst prepared in Example 3 of the present invention at different current densities;

[0031] Figure 6 This is a SEM morphology image of the β-MnO2 catalyst prepared in Comparative Example 1 of the present invention;

[0032] Figure 7 The XRD pattern of the β-MnO2 catalyst prepared in Comparative Example 1 of the present invention;

[0033] Figure 8 This is the oxygen reduction (ORR)-LSV performance curve of the β-MnO2 catalyst prepared in Comparative Example 1 of the present invention.

[0034] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0035] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0036] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0037] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0038] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0040] See also Figure 1-8 As shown, in this embodiment, a method for preparing a catalyst for improving the discharge performance of a metal fuel cell by inducing a rare earth-induced phase change of a manganese-based material is provided, comprising the following steps:

[0041] Step (1): preparing a monohydrated manganese sulfate solution, and adding ammonium persulfate and ammonium sulfate according to a molar concentration ratio, and magnetically stirring until the solution is completely dissolved to form a mixed solution ①;

[0042] Step (2): adding cerium nitrate according to the molar ratio to the mixed solution ① obtained in step (1), and continuing stirring for 1-2 hours, and mixing evenly to obtain a mixed solution ②;

[0043] Step (3): transferring the rare earth doping precursor solution obtained in step (2) to a hydrothermal reaction vessel for hydrothermal reaction;

[0044] Step (4): After the hydrothermal reaction is completed, the reaction product is centrifuged and washed with deionized water and ethanol to remove impurities. Subsequently, after cooling, the reaction product is centrifuged, washed with deionized water and ethanol, and dried in a vacuum oven at 50-80°C for 8-12 hours. After drying, the final α-MnO2 nanorod catalyst is obtained.

[0045] In one specific embodiment, the molar concentration ratio of the manganese sulfate monohydrate solution, ammonium persulfate and ammonium sulfate used in step (1) is 1:1:2.

[0046] In one specific embodiment, the magnetic stirring time in step (1) is 0.5-2h.

[0047] In one specific embodiment, the molar ratio of cerium nitrate in step (2) to the mixed solution ① is (0.1-0.5:1).

[0048] In a specific embodiment, the hydrothermal reaction temperature in step (3) is 120-140° C., and the reaction time is 10-12 h.

[0049] In one specific embodiment, the catalyst in step (4) has a rod-shaped nanostructure with a particle diameter of 20-50 nm and a length of 100-600 nm.

[0050] In a specific embodiment, the vacuum temperature in step (4) is 50-80° C., and the drying time is 8-12 hours.

[0051] The present invention will now be further described in detail with reference to embodiments.

[0052] It should be noted that all raw materials in the examples of the present invention were obtained through commercial sources.

[0053] Embodiment 1: A method for preparing a catalyst for improving the discharge performance of a metal fuel cell by inducing a rare earth phase change of a manganese-based material is provided, comprising the following steps:

[0054] Step (1): prepare 75 mL of 0.065 M manganese sulfate monohydrate solution, add 0.065 M ammonium persulfate and 0.13 M ammonium sulfate in a molar ratio of 1:2, and stir for 0.5 hour to fully mix the materials to form a stable mixed solution①;

[0055] Step (2): adding cerium (IV) nitrate to the mixed solution ① at a molar ratio of cerium (IV) nitrate to manganese sulfate of 0.1:1, and stirring for 2 hours to ensure the uniformity of rare earth cerium doping, and forming a mixed solution ②;

[0056] Step (3): transfer the doped mixed solution ② to a 100 mL hydrothermal reactor at room temperature and heat it at 140° C. for 12 hours to complete the phase transition of the material from β-phase MnO2 to α-phase MnO2;

[0057] Step (4): After the reaction is completed, the product is centrifuged and the impurities are washed with deionized water and ethanol. The product is dried in a vacuum oven at 60° C. for 12 hours to finally obtain a-MnO2 nanorods with a diameter of 40 to 50 nm and a length of about 500 to 600 nm.

[0058] Example 2: A method for preparing a catalyst for improving the discharge performance of a metal fuel cell by inducing a rare earth phase change in a manganese-based material is provided, comprising the following steps:

[0059] Step (1): prepare 75 mL of 0.065 M manganese sulfate monohydrate solution, add 0.065 M ammonium persulfate and 0.13 M ammonium sulfate in a molar ratio of 1:2, and stir for 0.5 hour to fully mix the materials to form a stable mixed solution①;

[0060] Step (2): adding cerium (IV) nitrate to the mixed solution ① at a molar ratio of cerium (IV) nitrate to manganese sulfate of 0.2:1, and stirring for 2 hours to ensure the uniformity of rare earth cerium doping, and forming a mixed solution ②;

[0061] Step (3): transfer the doped mixed solution ② to a 100 mL hydrothermal reactor at room temperature and heat it at 140° C. for 12 hours to complete the phase transition of the material from β-phase MnO2 to α-phase MnO2;

[0062] Step (4): After the reaction is completed, the product is centrifuged and the impurities are washed with deionized water and ethanol. The product is dried in a vacuum oven at 60° C. for 12 hours to finally obtain a-MnO2 nanorods with a diameter of 20 to 30 nm and a length of about 100 to 200 nm.

[0063] Example 3: A method for preparing a catalyst for improving the discharge performance of a metal fuel cell by inducing a rare earth phase change in a manganese-based material is provided, comprising the following steps:

[0064] Step (1): prepare 75 mL of 0.065 M manganese sulfate monohydrate solution, add 0.065 M ammonium persulfate and 0.13 M ammonium sulfate in a molar ratio of 1:2, and stir for 0.5 hour to fully mix the materials to form a stable mixed solution①;

[0065] Step (2): adding cerium (IV) nitrate to the mixed solution ① at a molar ratio of cerium (IV) nitrate to manganese sulfate of 0.3:1, and stirring for 2 hours to ensure the uniformity of rare earth cerium doping, and forming a mixed solution ②;

[0066] Step (3): transfer the doped mixed solution ② to a 100 mL hydrothermal reactor at room temperature and heat it at 140° C. for 12 hours to complete the phase transition of the material from β-phase MnO2 to α-phase MnO2;

[0067] Step (4): After the reaction is completed, the product is centrifuged and the impurities are washed with deionized water and ethanol. The product is dried in a vacuum oven at 60° C. for 12 hours to finally obtain a-MnO2 nanorods with a diameter of 20 to 30 nm and a length of about 200 to 300 nm.

[0068] Morphology and structure characterization (TEM and XRD analysis)

[0069] The transmission electron microscope (TEM) image of the rare earth Ce-doped manganese dioxide (Ce-MnO2) prepared in this embodiment is as follows: Figure 1 As shown in the figure, it can be observed that the synthesized manganese dioxide presents a typical nanorod-like structure, which is conducive to increasing the specific surface area of ​​the material and providing more active sites for the oxygen reduction reaction (ORR). In addition, the length and diameter of the rod-like structure are controlled between 20-50nm and 100-600nm, ensuring excellent conductivity and catalytic stability.

[0070] Further X-ray diffraction (XRD) analysis (such as Figure 2 As shown in the figure, the crystal structure of the material was characterized in detail. The diffraction peaks at 12.74°, 18.06°, 28.74°, 36.59°, 37.63°, 42.03°, 49.89°, 56.18°, 60.24°, and 69.60° correspond to the (110), (200), (310), (400), (121), (301), (411), (600), (521), and (451) crystal planes of α-MnO2, respectively. Compared with the β-phase MnO2 in Comparative Example 1, the material of this embodiment undergoes a significant crystal phase transformation, and the β-phase MnO2 is successfully transformed into a more stable α-phase MnO2 with higher electrocatalytic performance. This crystal phase change not only improves the stability of the material, but also improves its electrochemical activity.

[0071] Electrocatalytic performance evaluation

[0072] In the electrochemical performance test, 0.1M potassium hydroxide electrolyte was used to test the oxygen reduction reaction (ORR) of Ce-MnO2. During the test, the rotation speed of the electrode was set to 1600rpm to ensure that the oxygen in the solution was fully diffused. The obtained linear sweep voltammetry (LSV) curve is shown in Figure 3 As shown, the results show that the half-wave potential of Ce-MnO2 prepared in this example reaches 0.802V, which is significantly improved compared with β-phase MnO2. This shows that Ce-MnO2 exhibits excellent electrocatalytic performance in ORR and has higher oxygen reduction activity. The process of doping Ce effectively improves the conductivity of α-MnO2 and the utilization rate of active sites.

[0073] Application performance testing in aluminum-air batteries

[0074] In order to verify the practical application performance of Ce-MnO2 catalyst, it was prepared into a catalytic membrane and rolled with a nickel mesh and a waterproof breathable layer to form an air electrode. The electrode was used in an aluminum-air battery and discharged in an electrolyte of 4M potassium hydroxide + 0.025M sodium stannate. The test results are shown in Figure 4 As shown, at a current density of 20 mA cm -2 The discharge voltage of the electrode was stabilized at 1.38 V, indicating its high efficiency energy output capability in practical applications.

[0075] Discharge stability test at different current densities

[0076] To further evaluate the performance of Ce-MnO2 under different working conditions, we conducted discharge tests on the electrode at multiple current densities. Figure 5 As shown, at 5, 10, 20, 30, 40, 50 mA cm -2Under the current density condition, the discharge voltages were 1.61V, 1.50V, 1.37V, 1.26V, 1.19V and 1.13V respectively. The results show that no matter how the current density changes, the catalyst can maintain stable discharge performance and show good durability and stability. This shows that Ce-MnO2 can still maintain excellent electrocatalytic performance under high load conditions, making it an ideal choice for the positive electrode material of aluminum-air batteries.

[0077] Example 4: A method for preparing a catalyst for improving the discharge performance of a metal fuel cell by inducing phase change of a rare earth-induced manganese-based material is provided, comprising the following steps:

[0078] Step (1): prepare 75 mL of 0.065 M manganese sulfate monohydrate solution, add 0.065 M ammonium persulfate and 0.13 M ammonium sulfate in a molar ratio of 1:2, and stir for 0.5 hour to fully mix the materials to form a stable mixed solution①;

[0079] Step (2): adding cerium (IV) nitrate to the mixed solution ① at a molar ratio of cerium (IV) nitrate to manganese sulfate of 0.4:1, and stirring for 2 hours to ensure the uniformity of rare earth cerium doping, and forming a mixed solution ②;

[0080] Step (3): transfer the doped mixed solution ② to a 100 mL hydrothermal reactor at room temperature and heat it at 140° C. for 12 hours to complete the phase transition of the material from β-phase MnO2 to α-phase MnO2;

[0081] Step (4): After the reaction is completed, the product is centrifuged and the impurities are washed with deionized water and ethanol. The product is dried in a vacuum oven at 60° C. for 12 hours to finally obtain a-MnO2 nanorods with a diameter of 30 to 40 nm and a length of about 200 to 300 nm.

[0082] Example 5: A method for preparing a catalyst for improving the discharge performance of a metal fuel cell by inducing a rare earth phase change of a manganese-based material is provided, comprising the following steps:

[0083] Step (1): prepare 75 mL of 0.065 M manganese sulfate monohydrate solution, add 0.065 M ammonium persulfate and 0.13 M ammonium sulfate in a molar ratio of 1:2, and stir for 0.5 hour to fully mix the materials to form a stable mixed solution①;

[0084] Step (2): adding cerium (IV) nitrate to the mixed solution ① at a molar ratio of cerium (IV) nitrate to manganese sulfate of 0.5:1, and stirring for 2 hours to ensure the uniformity of rare earth cerium doping, and forming a mixed solution ②;

[0085] Step (4): transfer the doped mixed solution ② to a 100 mL hydrothermal reactor at room temperature and heat it at 120° C. for 10 hours to complete the phase transition of the material from β-phase MnO2 to α-phase MnO2;

[0086] Step (5): After the reaction is completed, the product is centrifuged and the impurities are washed with deionized water and ethanol. The product is dried in a vacuum oven at 60° C. for 12 hours to finally obtain a-MnO2 nanorods with a diameter of 30 to 40 nm and a length of about 300 to 400 nm.

[0087] Comparative Example 1: A method for preparing a β-MnO2 catalyst, comprising the following steps:

[0088] Step (1): Prepare 75 mL of 0.065 M manganese sulfate monohydrate solution, dissolve 0.065 M ammonium persulfate and 0.13 M ammonium sulfate, and stir for 0.5 h.

[0089] Step (2): The homogeneous solution obtained in step (2) was transferred to a 100 mL lined hydrothermal reactor at room temperature and heated at 140°C for 12 hours. After cooling, the solution was centrifuged, washed with deionized water and ethanol, and dried in a vacuum oven at 60°C for 12 hours to obtain a-MnO2 rod-like structures with a diameter of 100 to 120 nm and a length of about 1 to 2 μm.

[0090] Morphological characterization (SEM analysis)

[0091] The manganese dioxide (β-MnO2) prepared in this comparative example is shown in the scanning electron microscope (SEM) image. Figure 6 As shown. It can be observed from the figure that the obtained manganese dioxide presents a rod-like structure with a length of 1 to 2 μm. This large micron-sized size results in a relatively low specific surface area, reducing the active sites exposed at the reaction interface. This indicates that the undoped cerium β-phase MnO2 lacks structural optimization, which is not conducive to improving the catalytic performance of the oxygen reduction reaction (ORR). In addition, the larger size makes it perform poorly in terms of conductivity and electrochemical activity, limiting its application in metal fuel cells.

[0092] Crystal structure characterization (XRD analysis)

[0093] The crystal structure of the material was analyzed by X-ray diffraction (XRD) test. Figure 7As shown. The diffraction peaks at 28.64°, 37.31°, 40.95°, 42.76°, 46.04°, 56.59°, 59.30°, 64.77°, 67.16° and 72.18° correspond to the (110), (101), (200), (111), (210), (211), (220), (002), (310) and (301) crystal planes of β-MnO2, respectively. These typical diffraction peaks confirm that the material is a β-phase crystalline structure. However, compared with α-MnO2, the crystal structure of β-phase MnO2 is more compact and stable, but its electrochemical activity is poor. This structural characteristic of β-phase MnO2 results in it being unable to provide sufficient active sites in the oxygen reduction reaction, limiting its catalytic performance.

[0094] Electrochemical performance test

[0095] In order to further verify the electrochemical performance of β-MnO2, this example carried out an oxygen reduction reaction (ORR) test in 0.1M potassium hydroxide (KOH) electrolyte, and the linear sweep voltammetry (LSV) curve obtained by the test was as follows: Figure 8 As shown. From the test results, it can be seen that the half-wave potential of the β-MnO2 is 0.614V, which is significantly lower than the 0.802V of the Ce-MnO2 catalyst in Example 3, a decrease of 188mV. This result shows that the oxygen reduction catalytic activity of β-MnO2 is poor. In addition, the limiting current density of β-MnO2 is also low, further indicating that the catalytic performance of this material under high load conditions is insufficient.

[0096] Comparative Example Compared with the Ce-doped α-MnO2 catalyst in Example 3, the β-MnO2 in this comparative example exhibits obvious performance disadvantages. First, the larger rod-like structure of β-MnO2 leads to a small specific surface area and reduced active sites; secondly, although its compact crystal structure is stable, it lacks sufficient active sites to support efficient oxygen reduction reactions. The results of electrochemical tests show that the half-wave potential of β-MnO2 is lower than that of Ce-MnO2, and the catalytic activity is insufficient to meet the requirements of efficient fuel cell cathode materials.

[0097] The present invention is not limited to the above-mentioned embodiments. Anyone should be aware that any structural changes made under the enlightenment of the present invention, and any technical solutions that are the same or similar to the present invention, fall within the protection scope of the present invention. The technology, shape, and structural parts not described in detail in the present invention are all well-known technologies.

Claims

1. A method for preparing a catalyst for improving the discharge performance of metal fuel cells by rare earth-induced phase change of manganese-based materials, characterized in that: The following steps are involved: Step (1): preparing a monohydrated manganese sulfate solution, and adding ammonium persulfate and ammonium sulfate according to a molar concentration ratio, and magnetically stirring until the solution is completely dissolved to form a mixed solution ①; Step (2): adding cerium nitrate according to the molar ratio to the mixed solution ① obtained in step (1), and continuing stirring for 1-2 hours, and mixing evenly to obtain a mixed solution ②; Step (3): transferring the rare earth doping precursor solution obtained in step (2) to a hydrothermal reaction vessel for hydrothermal reaction; Step (4): After the hydrothermal reaction is completed, the reaction product is centrifuged and washed with deionized water and ethanol to remove impurities. Subsequently, after cooling, the reaction product is centrifuged, washed with deionized water and ethanol, and dried in a vacuum oven at 50-80°C for 8-12 hours. After drying, the final α-MnO2 nanorod catalyst is obtained.

2. The method for preparing a catalyst for improving the discharge performance of metal fuel cells by rare earth-induced phase change of manganese-based materials according to claim 1, characterized in that: The molar concentration ratio of the manganese sulfate monohydrate solution, ammonium persulfate and ammonium sulfate used in step (1) is 1:1:

2.

3. The method for preparing a catalyst for improving the discharge performance of metal fuel cells by rare earth-induced phase change of manganese-based materials according to claim 1, characterized in that: The magnetic stirring time in step (1) is 0.5-2h.

4. The method for preparing a catalyst for improving the discharge performance of metal fuel cells by rare earth-induced phase change of manganese-based materials according to claim 1, characterized in that: The molar ratio of cerium nitrate to mixed solution ① in step (2) is (0.1-0.5:1).

5. The method for preparing a catalyst for improving the discharge performance of metal fuel cells by rare earth-induced phase change of manganese-based materials according to claim 1, characterized in that: In step (3), the hydrothermal reaction temperature is 120-140° C., and the reaction time is 10-12 h.

6. The method for preparing a catalyst for improving the discharge performance of metal fuel cells by rare earth-induced phase change of manganese-based materials according to claim 1, characterized in that: The catalyst in step (4) has a rod-like nanostructure, a particle diameter of 20-50 nm, and a length of 100-600 nm.

7. The method for preparing a catalyst for improving the discharge performance of metal fuel cells by rare earth-induced phase change of manganese-based materials according to claim 1, characterized in that: The vacuum temperature in step (4) is 50-80° C., and the drying time is 8-12 hours.

8. A catalyst for improving the discharge performance of a metal fuel cell by rare earth-induced phase change of a manganese-based material, prepared by the method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Air electrode used in aluminum-air battery and preparation method of air electrode

    CN104505520A

  • Cerium-manganese composite oxide catalyst as well as preparation method and application thereof

    CN107519861A

  • Alpha-MnO2 oxygen reduction catalyst and preparation method thereof and metal-air battery

    CN108695520A

  • Manganese dioxide nanowire loaded noble metal catalyst as well as preparation method and application thereof

    CN115888709A

Cited By

  • Ce-alpha-MnO2 / CNTs nanowire and preparation method and application thereof, aqueous zinc ion battery positive plate and preparation method thereof, and aqueous zinc ion battery

    CN122276842A